Pengembangan Program Aplikasi Enhanced Machine Control dengan Python untuk Metode Interpolasi Newton - Gunawan, Alexander A. S.; Linggarjati, Jimmy (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Nowadays, one of industrial main problems is the flexibility of machines to be customized since they are designed based on certain standard. This research develops software for CNC (Computer Numerically Controlled) machine in order to execute the Newton Interpolation using Python. The platform used in the CNC machine is EMC (Enhanced Machine Control) and GUI (Graphical User Interface) AXIS on the operating system Linux Ubuntu. The Newton interpolation is used to create a curve based on several point determined by user. By converting this curve into G-Code, which could be read by CNC machine, the machine can move according to curve designed by user. This research is an initial study to customize the CNC machine and will continue to fulfill the user needs. This research obtained a program that is able to run well up to 4 input pairs. The higher number inputs will cause the oscillation in the interpolation curve.